Practices of handling audio - Ibrahim, Adamu Abubakar; Bhatti, Zeeshan; Zeki, Akram M. (IIUM Press, 2015)
Digital audio enables the records, storage and processing of sound (Dongge et al., 2001). IT allows for flexible handling of stored information, by encoding the information in a signal. This is done by passing sound through an analog-to-digital form and allows for reproduction of uncompressed or compressed sound (Adam et al., 2000). Digital audio or an audio data format with defined storage layer.